Legal Protection in the Use of Land for Mining Activities - Alpi Sahari (Randwick International of Social Science Journal, 2022)
Crime in the form of land use in the mining sector has experienced an alarming development. This study aims to reveal what legal remedies need to be done in land use. The data collected in this study used a normative juridical method. The results of the study indicate that there are strategies to overcome obstacles in the law enforcement process in mining practices, namely: First, to increase the professionalism and ability of law enforcement officials in investigating illegal mining crimes through education and training. Second, increasing the operationalization of illegal mining law enforcement by perfecting SOPs (Standard Operating Procedures), and field guidelines (Juklap) for handling illegal mining crimes. Third, increasing cooperation with related agencies by drafting an MoU (Memorandum of Understanding) and consistently and continuously coordinating efforts to optimize the synergy of illegal mining crimes. It is concluded that to protect the law against land use, of course, it is necessary to have the role of all relevant legal civil servants in directing land use properly.